Are spiritual, ethical, and eating qualities of poultry meat influenced by current and frequency during electrical water-bath stunning? - Hayat, Muhammad Nizam; Kumar, Pavan; Sazili, Awis Qurni (Elsevier, 2023)
With the continuous rise of Muslim and Jewish populations and their increasing preference for ritually slaughtered poultry meat, the industry is forced to redefine its existing product-centric quality standard toward a new consumer-centric dimension of quality. The new dimension is mainly attributed to ensuring animal welfare and ethical treatment (ethical quality), spiritual quality (such as halal status, cleanliness), and eating quality standards set by religion. To meet consumer quality requirements while maintaining high production performance, the industry has incorporated newer technologies that are compatible with religious regulations such as stunning methods like electrical water bath stunning. However, the introduction of new techniques such as electrical water bath stunning has been met with mixed reactions. Some religious scholars have banned the use of any stunning methods in religious slaughter, as halal status is believed to be compromised in cases where birds have been stunned to death before slaughter. Nevertheless, some studies have shown the positive side of the electrical water bath stunning procedure in terms of preserving eating, ethical, and spiritual quality. Therefore, the present study aims to critically analyze the application of various aspects of electrical water bath stunning such as current intensity and frequency on various quality attributes, namely, ethical, spiritual, and eating quality of poultry meat.